Website Cartoon sebagai Media Perlawanan : (Analisis Semiotika Greimas pada Webtoon Just Friends) - Sekartaji Anisa Putri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Various ideologies are contested through the media. Various critical thoughts color several media texts to fight domination. Just like the heterodoxy bromance value against the orthodoxy value of masculine domination through the Just Friends website cartoon. The webtoon can provide information to the public as users of bromance values which can free them from the pressure of dominant values. This study aims to explore the form of bromance resistance as heterodoxy on the Just Friends webtoon. This study uses Greimas semiotic analysis method with samples of two episodes which can be accessed free of charge via the LINE Webtoon. The analysis was carried out by conducting narrative structure analysis, actant analysis and deep structure analysis. The research findings or results show that the existing resistance is carried out both directly and indirectly through narration and webtoon visualization. Bromance's resistance to the doxy of masculine domination is illustrated through the presence of femininity. In conclusion, there are forms of heterodoxy bromance resistance in the Just Friends webtoon.